Cathodically activated Au/TiO2 nanocomposite synthesized by a new facile solvothermal method: An efficient electrocatalyst with Pt-like activity for hydrogen generation. (10th November 2018) - Mezni, Amine; Ibrahim, Mohamed M.; El-Kemary, Maged; Shaltout, Abdallah A.; Mostafa, Nasser Y.; Ryl, Jacek; Kumeria, T.; Altalhi, Tariq; Amin, Mohammed A.
Abstract: We report here a facile, template-free and one-step solvothermal approach for the synthesis of high-temperature stable gold/titania nanocomposite (NCs), providing a new, simple, quick and inexpensive wet-chemical route. Our approach is based on the assembly of gold salt and titanium butoxide in dimethyl sulfoxide (DMSO). Also, we present here, for the first time, a cathodically activated Au/TiO2 catalyst with Pt/C activity for the hydrogen evolution reaction (HER) in 0.5 M H2 SO4 in the dark. The as-prepared (unactivated) Au/TiO2 NCs exhibits considerable electrocatalytic activity for H2 generation in the dark, with a low onset potential ( E HER ) of −64 mV vs. RHE, a Tafel slope (- b c ) of 60 mV dec −1 and an exchange current density ( j o ) of 0.12 mA cm −2 . Long-term stability and durability tests in 0.5 M H2 SO4, employing cyclic voltammetry technique (10, 000 of repetitive cycling) and 72 h of chronoamperometry measurements at a high cathodic potential (cathodic activation), reveal that the electrocatalyst activates during such aging processes yielding an activated Au/TiO2 catalyst with Pt/C-like activity for H2 generation ( E HER -3 mV, - b c : 35 mV dec −1, and j o : 0.95 mA cm −2 ). The outstanding HER activity of the activated catalyst is discussed.